Blind as a Bat: [Un]seeing the Visio Dei in the Granum Sinapis Diagrams. Issue 1 (2nd January 2019) - Liston-Kraft, Philip
ABSTRACT: The Granum Sinapis – the 'Mustard Seed' – an early fourteenth century German poem, is a concise expression of the mystical and paradoxical precepts of Meister Eckhart. To find the way into the nothingness of God's mystery, one must pursue the path into the desert– a path without a route leading into a space with no boundaries. The composition was given its title by a Latin scholar whose scholastic commentary was transmitted along with the poem. Appended to the commentary are two crude diagrams, one, an empty circle, the other a set of concentric circles, that in their simplicity both mirror the poem as well as provide a final, eloquent gloss on the interaction between the apophatic theologies of Dionysius the Areopagite and Meister Eckhart. Like the vision of the bat looking into the sun, so does human understanding fail when contemplating God. Yet it is precisely through the medium of blindness that man comes closest to union with the divine.